2021
DOI: 10.1177/02666669211056926
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing through Social Networking Sites (SNSs): A Study of Pakistani Research Students

Abstract: The present study investigated the knowledge-sharing behavior of library and information management researchers, using the lens of the theory of planned behavior. The study is quantitative and adopted a survey questionnaire as a data collection technique. The snowball sampling technique was considered suitable to recruit respondents to the study. Data were analyzed with the help of SPSS (20.0) and the ADANCO (2.0.1). The research findings confirm that subjective norms and perceived behavioral control have a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The results of the validation analysis in this study demonstrated that perceived behavioral control and perceived security had a positive and significant influence on browsing information in social Q&A communities, with path coefficients of 0.50 and 0.24 for perceived behavioral control, perceived security, and browsing information, it can be concluded that perceived behavioral control is the predominant consideration for users when browsing information in social Q&A communities. Perceived behavioral control is the perception of the difficulty of performing the behavior, indicating that for the user, browsing information meets their abilities and expectations, which is consistent with the findings of Nader, Hashmi (Safa and Von Solms, 2016;Hashmi et al, 2021). Browsing as a basic way for users to participate in social Q&A communities, and intent to use when users feel safe with online communities (Ha and Pan, 2018), more users are inclined to visit online platforms that pay attention to the protection of their personal information, such as their ID, account information, and phone number, Zhihu, for instance, offers a browsing-only mode in which no personal information is collected, allowing users to get an initial experience of the platform, and thus perceived security influences users' willingness to browse, a finding similar to some other researchers (Klobas et al, 2019;Maqableh et al, 2021).…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 83%
“…The results of the validation analysis in this study demonstrated that perceived behavioral control and perceived security had a positive and significant influence on browsing information in social Q&A communities, with path coefficients of 0.50 and 0.24 for perceived behavioral control, perceived security, and browsing information, it can be concluded that perceived behavioral control is the predominant consideration for users when browsing information in social Q&A communities. Perceived behavioral control is the perception of the difficulty of performing the behavior, indicating that for the user, browsing information meets their abilities and expectations, which is consistent with the findings of Nader, Hashmi (Safa and Von Solms, 2016;Hashmi et al, 2021). Browsing as a basic way for users to participate in social Q&A communities, and intent to use when users feel safe with online communities (Ha and Pan, 2018), more users are inclined to visit online platforms that pay attention to the protection of their personal information, such as their ID, account information, and phone number, Zhihu, for instance, offers a browsing-only mode in which no personal information is collected, allowing users to get an initial experience of the platform, and thus perceived security influences users' willingness to browse, a finding similar to some other researchers (Klobas et al, 2019;Maqableh et al, 2021).…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 83%
“…Another research indicated that social media activities influence purchase intention, while subjective norms and perceived behavioral control play a mediating role ( Sun and Xing, 2022 ). Meanwhile, research conducted in the Pakistani context showed that social media use enhanced pre-service teachers’ subjective norms for their professional development ( Hashmi et al, 2021 ). Therefore, the finding of our study confirms that the social media-based community of inquiry is useful for linking subjective norms such as peers, class fellows, and colleagues of pre-service teachers to enhance their intentions toward social justice and equity in education.…”
Section: Discussionmentioning
confidence: 99%